Vascular endothelial dysfunction in sickle cell disease by brachial artery flow mediated dilatation - Raghuwanshi, Pranav Kumar; Raghuvanshi, Somnath Singh (Asian Journal of Medical Sciences, 2014)
Objective: The present study was conducted aiming to assess endothelial function in sickle cell disease (SS), sickle cell trait(SA) and compare to endothelial dysfunction between sickle cell anemia (SS), sickle cell trait (SA) cases and control (AA) patients to evaluate correlation of endothelial dysfunction. Methods: The study population comprised of, total 25 cases having sickle cell disease and sickle cell trait and 25 age and sex matched normal control. Endothelial dysfunction as assessed by brachial artery flow mediated dilatation by colour Doppler (non-invasive method)by using Siemens Sonoline 500. Statistical analysis was performed using Software Statistical Package for Social Sciences (SPSS) version 20, and P value of less than 0.05 was considered as statistically significant at 95% confidence intervals. Results: Significant difference were observed in FMD (flow mediated vasodilatation) in case and control group (p<0.05), also significant difference was demonstrated between AS and SS group. Conclusion: The percentage of flow mediated dilatation of vessel is a marker of endothelial function was significantly lower in cases as compared to controls and was also lower in AS & SS when compared to control group & significantly lower in SS group than AS group. Asian Journal of Medical Science, Volume-5(3) 2014: 105-107 http://dx.doi.org/10.3126/ajms.v5i3.9445